Multi-Media Tools and Service Delivery in Academic Libraries: A Case Study of Bishop Berham University. - Barigye, Damas (Kabale University, 2025)
The study was about multimedia, tools, and services in academic libraries at Bishop Barham University. The study was guided by objectives namely; To Investigate the current multi-media tools available in the library of Bishop Berham University, to find out how multi-media tools are utilized within the library of Bishop Berham University, to Identify challenges faced while utilizing multi-media tools in the library in Bishop Barham university, to establish the challenges of accessing credit by SME’s in Bishop Barham university, and to identify the strategies to improve Credit Accessibility in Bishop Barham university. A cross-sectional design was used in the study. The researcher used both Primary and secondary data. Secondary data was collected from the university library. The researcher got information from different and related sources or scholars, magazines, journals, and websites that all point and relate to this study, and information from the university library. The study also found that The researcher considered the sex, age, and years of study of respondents. This biographic data was essential for the researcher and the study to describe the best respondents selected for the study. Respondents outlined massive sensitization, which was identified as the best solution among the respondents. Information availability was identified to have played a very big role. The study concludes The study results on the current multi-media tools available in the library of Bishop Berham University Data collected multi-media tools available shows that most of the respondents were Computers represented 67% and this is in line with Britannica concise encyclopedia (2006) defined multimedia as a computer-based electronic system that affords users the opportunity to control, manipulate and integrate media elements like text, voiceover, video, infographics, and animation to ensure effective delivery of information. It helps the user in providing information from different media on one platform thus enhancing networking and resource sharing. Multimedia can also be seen as educational software involving animations, sounds, and text on CDs and DVDs.Therefore, it is suggested that Bishop Berham University has to focus more on the implementation and optimum utilization of library materials. Credit institutions that have facilitated the growth and performance of SMEs provide affordable interest rates; and train their clients on the relevancy of keeping financial information and, how to use the acquired loan for the intended purpose. The study recommended the policymakers formulate or update policies that prioritize funding and support for integrating multimedia tools in academic libraries.